2015
DOI: 10.1097/bcr.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Idiom “Functional Range of Motion” Related to Burn Recovery

Abstract: The term "functional" in burn rehabilitation has gained widespread use to describe a patient's recovery after burn injury. But what truly is "functional" when applied to a patient recovering from burn injury? A literature search was performed for information defining "functional" range of motion (ROM). Maximum upper and lower ROM values to perform a variety of daily activities were abstracted and compared with published outcomes of patient groups recovered from burn injury. Seventy references were reviewed lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…However, a standard classification scale or system to interpret the degree of joint limitation is not available in burn care. Therefore, the general interpretation of degree of limitation has a variable subjectivity or is classified by own description-and rating classification systems [32,33]. Korps found seven studies which classified the degree of limitation of a burn scar contracture.…”
Section: Discussionmentioning
confidence: 99%
“…However, a standard classification scale or system to interpret the degree of joint limitation is not available in burn care. Therefore, the general interpretation of degree of limitation has a variable subjectivity or is classified by own description-and rating classification systems [32,33]. Korps found seven studies which classified the degree of limitation of a burn scar contracture.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased ROM of joints in the lower limb restricts overall mobility and knee contractures limit ambulation, increase energy expenditure, increase the risk of falls, and increase wear on more other joints such as the hip, lumbar spine, and contralateral knee 10,15‐17 . Like OA, knee FC contributes to pain and stiffness and interferes with daily activities 15,18‐21 …”
Section: Introductionmentioning
confidence: 99%
“…Usually, traditional rehabilitation interventions in mainland China are provided after most wound areas are healed. In contrast, early rehabilitation in burn patients showed improvement in joint ROM and a shorter BICU LOS and in the hospital [2729]. According to the analysis in this study, we found that when early rehabilitation was performed within 7 days post-injury, severe burn patients could have fewer contractures of decreased severity.…”
Section: Discussionmentioning
confidence: 77%